Interpreting international politics - Lynch, Cecelia (New York : Routledge, 2014)
'Interpretive approaches to the study of international relations span not only the traditional areas of security, international political economy, and international law and organizations, but also emerging and newer areas such as gender, race, religion, secularism, and continuing issues of globalization. But how are we to bring interpretivist methods and concerns to bear on these topics? Cecelia Lynch focuses on the philosophy of science and conceptual issues that make work in international relations distinctly interpretive. This work both legitimizes and demonstrates the necessity of post- and non-positivist scholarship. Lynch address each of the major,'traditional,' subfields in International Relations, including International Law and Organization, International Security, and International Political Economy, situating, describing, and analyzing major interpretive works in each of these fields to draw out critical research challenges posed and progress in the field made by interpretive work. Furthermore, the book also pushes forward interpretive insights to areas that have entered the IR radar screen more recently, including race and religion, demonstrating how work in these areas can inform all subfields of the discipline and suggesting paths for future research'--
1. Interpretive concepts, goals, and processes in international relations -- 2. Interpreting international security -- 3. Interpreting international political economy -- 4. Interpreting international law and organization -- 5. Race, religion, histories, and futures in international relations.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: International relations; World politics; Electronic books